x+(x+1)=122-3(x+2)

Simple and best practice solution for x+(x+1)=122-3(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(x+1)=122-3(x+2) equation:


Simplifying
x + (x + 1) = 122 + -3(x + 2)

Reorder the terms:
x + (1 + x) = 122 + -3(x + 2)

Remove parenthesis around (1 + x)
x + 1 + x = 122 + -3(x + 2)

Reorder the terms:
1 + x + x = 122 + -3(x + 2)

Combine like terms: x + x = 2x
1 + 2x = 122 + -3(x + 2)

Reorder the terms:
1 + 2x = 122 + -3(2 + x)
1 + 2x = 122 + (2 * -3 + x * -3)
1 + 2x = 122 + (-6 + -3x)

Combine like terms: 122 + -6 = 116
1 + 2x = 116 + -3x

Solving
1 + 2x = 116 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
1 + 2x + 3x = 116 + -3x + 3x

Combine like terms: 2x + 3x = 5x
1 + 5x = 116 + -3x + 3x

Combine like terms: -3x + 3x = 0
1 + 5x = 116 + 0
1 + 5x = 116

Add '-1' to each side of the equation.
1 + -1 + 5x = 116 + -1

Combine like terms: 1 + -1 = 0
0 + 5x = 116 + -1
5x = 116 + -1

Combine like terms: 116 + -1 = 115
5x = 115

Divide each side by '5'.
x = 23

Simplifying
x = 23

See similar equations:

| n/30-2=3 | | 7=12-5x+4y | | 7f-3=39 | | x-3/5=-1 | | 46-2=8 | | 3x^4-14x^2-24=0 | | 50e-1=799 | | y-(-5)=9x+18 | | a/8-2=8 | | 2-x/2=8-x/3 | | 4(g+8)+7+4g= | | 11k-5=61 | | 8y=2x-48 | | 15y+10=85 | | u^3=27 | | 2-x+9=3x+8 | | (x-45)+(x-45)+(x-45)+2x=540 | | 3n+12=52 | | -3y=2x+12 | | 3(1.2b-1)+36=4.2 | | f(1)=1.5n+6 | | 9x-1=-6x+11 | | 12=-13+4y | | 8x-2=-2x+18 | | 13y+3=16y | | 4/5x-9=35 | | 10y^2+21y+2=0 | | -8x^2-40x+3=0 | | 5ln(x-3)=10 | | 1/2n-3=2/3n-1 | | (x^2)+1x+19=0 | | (2+5i)(4+3i)=0 |

Equations solver categories